2017
DOI: 10.3892/mmr.2017.7573
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivities of calbindin-D28k, calretinin and parvalbumin in the somatosensory cortex of rodents during normal aging

Abstract: Calbindin-D28k (CB), calretinin (CR) and parvalbumin (PV), which regulate cytosolic free Ca2+ concentrations in neurons, are chemically expressed in γ-aminobutyric acid (GABA)ergic neurons that regulate the degree of glutamatergic excitation and output of projection neurons. The present study investigated age-associated differences in CB, CR and PV immunoreactivities in the somatosensory cortex in three species (mice, rats and gerbils) of young (1 month), adult (6 months) and aged (24 months) rodents, using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…On the other hand, it is also abundant in the axons and terminals of fast firing, excitatory neurons, for example, of the sensory thalamus (e.g., Celio, 1990 ; Cruikshank et al, 2001 ). In accordance with previous studies on auditory (Long Evans rat: Ouda et al, 2008 ; human: Bu et al, 2003 ) and somatosensory cortex (mouse: Karetko-Sysa et al, 2014 ; mouse, gerbil, and rat: Ahn et al, 2017 ) we found slightly increasing PV levels in the sensory cortices of elderly gerbils compared to adult ones. This can be interpreted either as a result of increasing inhibition within the intracortical network or increasing excitatory input from the thalamus during aging (for review, e.g., Cruikshank et al, 2001 ; Ouda et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it is also abundant in the axons and terminals of fast firing, excitatory neurons, for example, of the sensory thalamus (e.g., Celio, 1990 ; Cruikshank et al, 2001 ). In accordance with previous studies on auditory (Long Evans rat: Ouda et al, 2008 ; human: Bu et al, 2003 ) and somatosensory cortex (mouse: Karetko-Sysa et al, 2014 ; mouse, gerbil, and rat: Ahn et al, 2017 ) we found slightly increasing PV levels in the sensory cortices of elderly gerbils compared to adult ones. This can be interpreted either as a result of increasing inhibition within the intracortical network or increasing excitatory input from the thalamus during aging (for review, e.g., Cruikshank et al, 2001 ; Ouda et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…Calbindin (CB) is a 28-kDa protein with six EF-hand Ca 2+ -binding domains, but only four are active and have rapid binding kinetics. In the brain, it can be found mainly in populations of γ-aminobutyric acid (GABA)-containing interneurons scattered throughout cortical layers but concentrated in supragranular layers; positive interneurons can also be identified in the hippocampus, where granule cells of the dentate gyrus and some CA1 pyramidal neurons are also immunoreactive to this protein, and in the hypothalamus [28,29,30,31]. In the cerebellum, CB is specifically and strongly expressed in Purkinje cells, and in some mammals, in Golgi cells [24,26].…”
Section: Cbps In the Central Nervous Systemmentioning
confidence: 99%
“…Calretinin. Calretinin (CR) is a less studied, 31-kDa protein with five active Ca 2+ binding domains that is distributed in a distinct but smaller population of cortical interneurons of the cerebral cortex, in some neurons of the thalamus, and in the granule cells and unipolar brush cells of the cerebellum [26,30,34,35]. CR -/- mice obtained through homologous recombination had impaired long-term potentiation in the hippocampus, while in the cerebellum, the alteration of granule cell excitability following CR depletion also led to altered CB activity and Ca 2+ homeostasis in Purkinje cells, resulting in a mild motor coordination impairment that is less pronounced than the one observed for CB knockout [24,32].…”
Section: Cbps In the Central Nervous Systemmentioning
confidence: 99%
“…In TRN, we saw uniformly dense populations of PV + cells with large immunonegative nuclei, which is characteristic of PV + labeling in TRN neurons (Fig 1D;(Arai et al, 1994;Celio, 1990;Csillik et al, 2005;Kirichenko et al, 2017). Likewise, the distribution of PV + cells in cortex was organized by layers and was comparatively more sparse ( Fig 1E; also see Van Brederode et al, 1991;Ahn et al, 2017). Despite the absence of PV + cell bodies in the midline thalamus, parvalbumin labeling was still abundant in the form of PV + puncta that were most often clustered near or between cell bodies ( Fig.…”
Section: Absence Of Pv + Cells In Midline Thalamusmentioning
confidence: 68%